REINTERPRETING NEW INSTITUTIONALISM THROUGH INSTITUTIONAL RESILIENCE - Lu, Shanshan; Azis, Yudi; Kurniawan, Meinanda; Sari, Rora Puspita (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2025)
New Institutionalism has long provided the core framework for understanding institutional formation and stability, emphasizing rules, norms, and legitimacy in shaping organizational behavior. However, traditional New Institutionalism focuses primarily on the logic of existence, explaining how institutions are created and maintained, while overlooking their logic of survival and logic of performance under dynamic change. This conceptual paper introduces Institutional Resilience Theory as a bridge linking New Institutionalism and Performance Regime Theory, revealing how institutions evolve from existence to performance. Institutional resilience—comprising learning, buffering, and adaptive capacities—enables institutions to sustain functionality under stress and transform stability into performance through feedback and interaction. The paper argues that performance represents a “resilient form of legitimacy,” thereby reinterpreting New Institutionalism from a dynamic perspective and extending its explanatory scope.